Behind the scenes of the Pfizer BioNTech covid-19 vaccine trial. (23rd February 2021) - Silberner, Joanne
Abstract : Never has the spotlight been as strong on a clinical trial as that on the Pfizer BioNTech vaccine, the first approved for covid-19. The BMJ spoke to its lead principal investigator, Stephen Thomas